STRATIGRAPHIC AND STRUCTURAL EVOLUTION OF THE SELENGA DELTA ACCOMMODATION ZONE, LAKE BAIKAL RIFT, SIBERIA - Scholz C.A.; Hutchinson D.R. (My University, 2000)
Seismic reflection profiles from the Lake Baikal Rift reveal extensive details about the sediment thickness, structural geometry and history of extensional deformation and syn-rift sedimentation in this classic continental rift. The Selenga River is the largest single source of terrigenous input into Lake Baikal, and its large delta sits astride the major accommodation zone between the Central and South basins of the lake. Incorporating one of the world's largest lacustrine deltas, this depositional system is a classic example of the influence of rift basin structural segmentation on a major continental drainage. More than 3700 km of deep basin-scale multi-channel seismic reflection (MCS) data were acquired during the 1989 Russian and the 1992 Russian–American field programs. The seismic data image most of the sedimentary section, including pre-rift basement in several localities. The MCS data reveal that the broad bathymetric saddle between these two major half-graben basins is underlain by a complex of severely deformed basement blocks, and is not simply a consequence of long-term deltaic deposition. Maximum sediment thickness is estimated to be more than 9 km in some areas around the Selenga Delta. Detailed stratigraphic analyses of the Selenga area MCS data suggest that modes of deposition have shifted markedly during the history of the delta. The present mode of gravity- and mass-flow sedimentation that dominates the northern and southern parts of the modern delta, as well as the pronounced bathymetric relief in the area, are relatively recent developments in the history of the Lake Baikal Rift. Several episodes of major delta progradation, each extending far across the modern rift, can be documented in the MCS data. The stratigraphic framework defined by these prograding deltaic sequences can be used to constrain the structural as well as depositional evolution of this part of the Baikal Rift. An age model has been established for this stratigraphy, by tying the delta sequences to the site of the Baikal Drilling Project 1993 Drill Hole. Although the drill hole is only 100 m deep, and the base of the cores is only 670 ka in age, ages were extrapolated to deeper stratigraphic intervals using the Reflection-Seismic-Radiocarbon method of Cohen et al. (1993). The deep prograding delta sequences now observed in the MCS data probably formed in response to major fluctuations in sediment supply, rather than in response to shifts in lake level. This stratigraphic framework and age model suggest that the deep delta packages developed at intervals of approximately 400 ka and may have formed as a consequence of climate changes affiliated with the northern hemisphere glaciations. The stratigraphic analysis also suggests that the Selenga Basin and Syncline developed as a distinct depocentre only during the past 2–3 Ma.